EFEKTIVITAS SENAM AEROBIK LOW IMPACT UNTUK MENINGKATKAN KEBUGARAN KARDIORESPIRASI PADA REMAJA: EFFECTIVENESS OF LOW IMPACT AEROBIC EXERCISE TO IMPROVE CARDIORESPIRATORY FITNESS IN ADOLESCENTS - Titan Pinasti Jungjunan; yoni Rustiana; Fendy Nugroho (Jurnal Nasional Fisioterapi, 2025)
Introduction: Cardiorespiratory fitness is an important indicator of physical health, mental health, and academic success, especially in adolescents. Many teenagers experience a decrease in cardiorespiratory fitness due to lack of physical activity, irregular diet, and lack of rest. Low impact aerobic gymnastics is one of the physical activities that can improve cardiorespiratory fitness through structured movements that aim to optimize the function of the heart, lungs, and blood vessels. Method: This study used a quantitative design with a one group pre-test post-test design with subjects totaling 23 teenagers who had met the inclusion and exclusion criteria. The instrument used is in the form of the Harvard Step Test to measure cardiorespiratory fitness. The hypothesis test used is the Wilcoxon test. Results: Based on the research results, a significant increase in fitness parameters measured by the Harvard Step Test p = <0.001 with an increase in the cardiorespiratory fitness index from 22.08 to 30.14. Knot: Low impact aerobic gymnastics is effective in improving cardiorespiratory fitness in teenagers with significant improvement.